Implementasi Kurikulum 2013 Pada Mata Pelajaran Alquran Hadits di MTs. Swasta Teladan Gebang Kab. Langkat - Danny Abrianto; Hasrian Rudi Setiawan; Ahmad Fuadi (Intiqad: Jurnal Agama dan Pendidikan Islam, 2018)
This paper aims to find out how in MTs. Swasta Teladan Gebang Kab. Langkat on Qur'anic Subjects Hadith implements the 2013 Curriculum in the Planning, Implementation and Assessment Phase. The results of this paper that Implementation of the 2013 Curriculum in the planning stage is appropriate for the Qur'anic Subjects of Hadith in MTs. Swasta Teladan Gebang Kab. Langkat with learning tools made by teachers, namely syllabus and Learning Implementation Plan (RPP).In the implementation phase of the 2013 curriculum, it cannot be carried out directly fully, except with a process and improvements that are carried out in stages. This means that the implementation of learning using the 2013 curriculum can only be done in the superior class, but in the regular class it cannot be carried out maximally. In the assessment phase, the teacher does not experience difficulties in assessing the Qur'anic Hadith subjects, only in the 2013 curriculum are written in detailed formats in carrying out student assessments every day. This format makes the assessment process difficult because the implementation of the assessment covers three aspects, including the assessment of knowledge, skills and attitudes.